Evaluation of the Effects of Anesthetics and Surgery on Sleep Quality in Patients Undergoing Posterior Spinal Instrumentation Surgery: A Prospective Randomised Clinical Trial - Selcan Akesen; Gökay Eken; Yücel Bilgin; Saltuk Buğra Güler; Elifgül Ulutaş (İstanbul Medical Journal)
Introduction: The aim of the study is to evaluate the impact of the anesthesia methods and surgical procedure on the sleep patterns and sleep quality of patients undergoing posterior spinal instrumentation, using the Pittsburgh Insomnia Rating Scale-20 (PIRS-20). Methods: A total of 40 patients, American Society of Anesthesiology I-III, aged 18 and over who underwent elective spinal posterior instrumentation were included. The patients were divided into two groups randomly-those with sevoflurane-remifentanil anesthesia and those with total intravenous anesthesia-using the closed envelope method. Patients were evaluated before and after surgery for sleep quality using the PIRS-20 one month before surgery and on the 7th day postoperatively, for pain using the Visual Analog Scale (VAS) recorded one night before surgery and the first hour postoperatively, and for anxiety using the State-Trait Anxiety Inventory (STAI) recorded one night before surgery and on the 7th day postoperatively. Results: When pre-operative and postoperative PIRS-20, VAS, and STAI scores were compared, no significant difference was observed between group T and group S (p>0.05). The VAS values in group S and group T decreased significantly over time (group S: p<0.001; group T: p=0.001, respectively). The STAI scores decreased significantly over time (p=0.001). The PIRS-20 values remained unchanged in groups S and T (p=0.132, p=0.828, respectively). Conclusion: The results of the study showed that while the type of anesthesia did not affect the quality of sleep in the group of patients receiving posterior instrumentation, the surgical procedure did influence pain reduction in both anesthesia methods.